COSMOARCHEOLOGY: ASTROPHYSICAL PROBES FOR NEW PHYSICS IN THE EARLY UNIVERSE - Khlopov, M. Yu. (Одеські астрономічні публікації, 2017)
The original Gamov’s Big Bang cosmology has evolved for the last decades to the modern cosmology, losing the direct relationship with the experimentally proven physical laws. It is the aim of cosmoparticle physics to study both the early Universe and the physics, governing its evolution, in the combination of their indirect cosmological, astrophysical and physical effects. Cosmoarcheology is the important branch of this research. It undertakes the Gedanken Experiment, tracing cosmological signatures for the new physics in the astrophysical data. The main ideas of the modern cosmology find their physical origin in the hypothetical processes in the early Universe: the total density is related to the result of inflation, the baryon density - to baryosynthesis and the dark matter - to primordial particles and/or fields generated before the 1 s of cosmological expansion. The physical mechanisms for these processes are based on predictions of particle theory. To specify the physical origin of the cosmological functions one needs the additional model-dependent cosmological effects, that can be referred to as the hidden functions of the modern cosmology. Cosmoarcheological analysis finds the spectrum of primordial black holes, inhomogeneous baryosynthesis and multicomponent dark matter as important signatures of the new physics in the early Universe, related to a wide class of physical realisations of cosmological models. Such analysis predicts new phenomena in the Universe, which can be the subject of astronomical discoveries in the next decades, such as mirror matter, 4th type of neutrino, or macroscopic antimatter in baryon asymmetrical Universe. In particular, it follows from this analysis, that the halo of our Galaxy can contain up to 100000 antimatter stars. Cosmoarcheological chains link the processes in the early Universe to the effects after the first second, which can be tested in the observations of the thermal background, of the baryon matter space distribution and chemical composition, of non-thermal electromagnetic backgrounds and cosmic rays. The important role of cosmoarcheological methods is illustrated on the example of the model of horizontal unification. The model proves that in no case the physically self-consistent realisation of inflation, baryosynthesis and dark matter can be reduced to these three phenomena only. Cosmoarcheological analysis of the additional cosmological consequences, following from such realisations, provides the principal possibility to reproduce the physics of early Universe in all its nontrivial complexity.